Deciphering molecular pathways driving cancer invasion and metastasis: advances and therapeutic prospects - Alshahrani, Aziza; Alsubait, Arwa; Asiri, Zahrah; Alghamdi, Sahar; Bin Saqyah, Sarah; Alqahtani, Tariq; Fitaihi, Rawan; Altuwaijri, Njoud; Jamous, Yahya F. (Frontiers in Oncology, 2025)
Metastasis is the primary cause of cancer-related mortality worldwide. This narrative review integrates recent advances in the molecular circuits orchestrating metastatic progression, encompassing epithelial–mesenchymal transition (EMT), organotropism, extracellular matrix remodeling, angiogenesis, hypoxia-inducible signaling, tumor-cell migration modes, and tumor–immune interactions through expert-guided literature selection. We examined therapeutic innovations that disrupt these pathways, including EMT modulators, matrix metalloproteinase inhibitors, VEGF/VEGFR-targeted regimens, hypoxia-activated prodrugs, and next-generation immunotherapies such as immune checkpoint blockade and chimeric antigen receptor T cells. Additionally, we discuss established nanotechnology-based delivery systems, advancing multi-omics integration, evolving single-cell analyses, and emerging CRISPR-Cas9 gene-editing applications as tools for improving metastasis detection, monitoring, and treatment. Despite this progress, translational obstacles persist, particularly regarding intratumoral heterogeneity, adaptive resistance, and limited preclinical model fidelity. Addressing these challenges requires biomarker-guided, multi-target therapeutic combinations, interdisciplinary collaboration, and globally inclusive clinical trials. This evidence underscores the importance of integrated strategies that simultaneously target intrinsic tumor plasticity and microenvironmental support to transform metastatic cancer outcomes.